1996
DOI: 10.1128/jvi.70.8.5668-5672.1996
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms involved in protection and recovery from influenza virus infection in immunodeficient mice

Abstract: We investigated the role of different lymphocyte subpopulations in the host defense reaction against influenza virus infection, taking advantage of various immunodeficient mouse strains. Whereas, following immunization, wild-type animals showed complete protection against challenge with a lethal dose of A/PR8/34 (PR8) virus, mice that lack both B and T cells but not NK cells (namely, scid and RAG2 ؊/؊ mice) did not display any protective effect in similar conditions. By contrast, J H D ؊/؊ mice devoid of B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Although recent studies demonstrated that cytotoxic T cells closely contributed to the elimination of pulmonary virus in the late phase in mice infected with influenza virus (3,6), it was also reported that the cooperative responses with antibody and cytotoxic T cells effectively contributed to the virus elimination (21,26) and that antibody response could also contribute to recovery from a pulmonary influenza virus infection (31). The most recent study showed that H5N1 influenza virus, a virulent strain for human and mouse, caused the systemic lethal infection with drastic lymphocytopenia (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies demonstrated that cytotoxic T cells closely contributed to the elimination of pulmonary virus in the late phase in mice infected with influenza virus (3,6), it was also reported that the cooperative responses with antibody and cytotoxic T cells effectively contributed to the virus elimination (21,26) and that antibody response could also contribute to recovery from a pulmonary influenza virus infection (31). The most recent study showed that H5N1 influenza virus, a virulent strain for human and mouse, caused the systemic lethal infection with drastic lymphocytopenia (37).…”
Section: Discussionmentioning
confidence: 99%
“…For investigating the immune response against influenza viruses, the HI assay determines protective humoral responses (8). Finally, in addition to HI assay results, assessment of the human T-cell responses against influenza virus infection has been reported previously to provide an important marker of protection (3,10,22). Until now, these assays have been performed mostly by applying live virus, hence necessitating the use of BSL-3 conditions for studying (potential) pandemic influenza virus.…”
Section: Introduction Of a New Influenza Virus In Humans Urges Quick mentioning
confidence: 99%
“…Recovery from influenza infection is dependent on the recruitment of proinflammatory leukocytes to sites of infection [9,10]. In particular, virus-specific T cells are essential for the clearance of influenza virus.…”
Section: Introductionmentioning
confidence: 99%